Intracellular delivery of 10-hydroxycamptothecin with targeted nanostructured lipid carriers against multidrug resistance. (27th May 2016) - Liu, Min; Chen, Didi; Mukerabigwi, Jean Felix; Chen, Sha; Zhang, Yuannian; Lei, Shaojun; Luo, Shiying; Wen, Zhili; Cao, Yu; Huang, Xueying; He, Hongxuan
Abstract: 10-Hydroxycamptothecin (HCPT) is a clinical therapy agent against hepatoma. The chemotherapy of HCPT is strongly obstructed by the emergence of multidrug resistance (MDR), serious systemic toxicity, malfunction of rapid phagocytic and renal clearance disorder which are undesirable for its chemotherapy. In this paper, a drug delivery system (DDS) for HCPT has been developed in order to overcome MDR. Nanostructured lipid carriers (NLC) coated with xyloglucan (XG) was prepared by soya oil and XG consisting of side chains with galactose residues, a terminal moiety that can be used to target HCPT to hepatoma. The therapeutic potential of XG-NLC/HCPT was investigated on HepG2/HCPT cells and on human tumor xenograft nude mouse model (implanted with HepG2/HCPT cells). XG-NLC/HCPT not only indicated superior cytotoxicity against the drug resistant HepG2 cells but also in vivo, generated a higher therapeutic effect. Systemic toxicity study demonstrated that the carrier reduced systemic toxicity. XG-NLC/HCPT proved a great potential to serve as DDS to overcome MDR of HepG2/HCPT cells. These results suggested that XG NLC/HCPT represent a promising carrier for drug delivery to the hepatoma and reverse the drug resistant of HepG2 cells and XG could be exploited as a potential targeting device for liver tissue.